2014
DOI: 10.1002/ange.201306489
|View full text |Cite
|
Sign up to set email alerts
|

C‐H‐Funktionalisierung über intramolekularen Hydridtransfer

Abstract: Gripping ligands: A series of fluoroalkoxy‐functionalized imidazol‐2‐ylidene ligands were synthesized by the alkylation of a range of commercially available azoles with hexafluoroisobutylene oxide. The deprotonation of these species with a strong base cleanly generated the free carbenes, which acted as tridentate chelating ligands (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(13 citation statements)
references
References 186 publications
0
12
0
1
Order By: Relevance
“…[1] However,o ur DFT analysish as shown that the here described intermolecular reactions are mechanistically quite different as they seem to involvet he B(C 6 F 5 ) 3 Lewis acid as av ery efficient hydride shuttling reagent between the components of our CÀHa ctivation/CÀCc oupling sequence under the here prevailing frustrated Lewis pair conditions. In the case of the reaction with ethyl acrylate, we have even observed as ubsequent H 2transfer reactiont hat leads to the analogousp roduct type as we observed from the amine + acetylenic ester reaction.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…[1] However,o ur DFT analysish as shown that the here described intermolecular reactions are mechanistically quite different as they seem to involvet he B(C 6 F 5 ) 3 Lewis acid as av ery efficient hydride shuttling reagent between the components of our CÀHa ctivation/CÀCc oupling sequence under the here prevailing frustrated Lewis pair conditions. In the case of the reaction with ethyl acrylate, we have even observed as ubsequent H 2transfer reactiont hat leads to the analogousp roduct type as we observed from the amine + acetylenic ester reaction.…”
Section: Discussionmentioning
confidence: 81%
“…[1][2][3] Frustrated Lewis pair chemistry [4] can make ac ontribution to this ongoingd evelopment,e specially by using the hydride acceptor abilities of the free boron Lewis acid, [5,6] for example, B(C 6 F 5 ) 3 , [7] in the active Lewisp airs. [1][2][3] Frustrated Lewis pair chemistry [4] can make ac ontribution to this ongoingd evelopment,e specially by using the hydride acceptor abilities of the free boron Lewis acid, [5,6] for example, B(C 6 F 5 ) 3 , [7] in the active Lewisp airs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a plausible mechanism for the tandem cyclization procedure was proposed on the basis of previous studies on intramolecular hydride transfer reactions (Scheme ) . Under acid conditions, the first THF ring could be formed after a substitution reaction to generate tricyclic compound A .…”
Section: Methodsmentioning
confidence: 99%
“…[6k] Based on these results,weenvisioned that a[1,5]-hydride shift [8] might also be feasible starting from as uitably functionalized keteniminium ion such as 6,w hich could be simply generated by protonation of the corresponding ynamide 5 (Scheme 2). Provided that this hydride shift would be operative, [9] selective,a nd faster than the trapping of the keteniminium ion with either its counter-anion or the starting ynamide,acarbocation 7 would be generated, which could then, hopefully,r eact intramolecularly with the enamide moiety formed after the hydride shift.…”
mentioning
confidence: 99%